Síntese e caracterização de catalisadores SnO2.Nb suportado em argila maranhense - Gonçalves, Cíntia Leite; Corazza, Marcos Lucio; Oliveira, Marcelo Moizinho; Rangel, José Hilton Gomes; Vasconcelos, Jomar Sales; De Figueredo, Gilvan Pereira; Longo, Elson [UNESP] (FapUNIFESP (SciELO), 2018)
The development and optimization of heterogeneous catalysts is a fundamental step to ensure the technical and economic feasibility of new materials created for a wide range of applications, including catalytic applications. The purpose of this study was therefore to synthesize and characterize clay materials from the state of Maranhão, Brazil, doped with tin and niobium oxides synthesized by the polymeric precursor method. The catalysts were characterized by X-ray diffraction (XRD), infrared spectroscopy (IR), scanning electron microscopy (SEM), nitrogen physisorption (BET), and energy dispersive X-ray spectroscopy (EDS). The results indicated that activating the clay mineral increased the specific surface area from 83.53 m2 g-1 to 155.2 m2 g-1, while doping with niobium reduced the specific surface area to 14.68 m2 g-1. The chemical composition of the material treated with nitric acid was found to limit the concentrations of some metals and increase the silica content. The XRD and IR analyses revealed the presence of niobium and tin in the clay matrix. Lastly, the method of synthesis adopted here proved to be efficient for the preparation of the supported catalyst (SnO2.Nb/clay).
Synthesis and characterization of SnO2.Nb catalysts supported on maranhão clay
Keywords: Maranhense clay; Nb; Polymeric precursor method; SnO2; Supported catalysts